Effective Vaccine Management: The Case of a Rural District in Ghana. (13th October 2019) - Osei, Eric; Ibrahim, Mohammed; Kofi Amenuvegbe, Gregory
Abstract : Background. The Effective Vaccine Management (EVM) initiative provides the platform needed to monitor and assess the vaccine supply chain system to identify strengths and weaknesses of the system at all levels to enhance the development of improvement plan to strengthen the system. This valuation was carried out in the Tolon District of the Northern Region, Ghana. Methods. A descriptive valuation of vaccine management was carried out in six vaccine stores in the Tolon District of Northern Ghana. We employed World Health Organization (WHO) assessment tools and procedures which consisted of desk reviews and interviews of cold chain managers to assess vaccine management practices in the district. Five out of the nine global assessment criteria were assessed and a minimum target level required for all criteria to meet the WHO standard was 80%. Results. None of the facilities assessed met the WHO benchmark of 80% for all but one criteria assessed. With regards to temperature control, the scores ranged from 42% at Kasuliyili CHPS Centre to 77% at the district store with an average district score of 60%. Stock management ranged between 11% at Wantugu Health Centre and 75% at Nyankpala Health Centre with district average score of 32%. Effective vaccine distribution scores ranged between 13% at Kasuliyili CHPS and 46% at Nyankpala Health Centre with an average district score of 27%. Only Nyankpala Health Centre had an acceptable score of 84% for vaccine management, whereas the lowest score for this indicator was 5% at Tolon Health Centre store with district average score of 53%. Information management and supportive functions scores ranged from 0% at Tolon Health Centre to 26% at the district store with the district average score of 16%. Nineteen (90.5%) of vaccine users had poor knowledge regarding temperature control and vaccine distribution. Conclusion. Effective vaccine management knowledge and practices are poor at Tonlon district and calls for urgent and pragmatic approaches such as training and re-training of vaccine users at all levels.